HUBUNGAN LUAR NEGERI INDONESIA ERA OTONOMI DAERAH. Studi Evaluasi Hubungan Sister Province (Provinsi Kembar) Jawa Tengah Dengan Negara Bagian Queensland Australia Periode Tahun 2000– 2007. - RENI WINDIANI, RENI WINDIANI (Program Magister Ilmu Politik, Universitas Diponegoro, 2011)
AbstractLaw number 32 / 2004 about Regional Government has open opportunity as an actor inforeign relation. The government of Central Java Province has utilized this opportunity conductingcooperation with government other countries such as Australia, Turkey, China, and Cambodia.Cooperation between Government of Central Java Province and government from othercountries is important to study because this is new phenomenon in foreign relation. An evalution studyis required to know the efficiency and effectivisnes of this policy.This research has focused on the cooperation among sister province that is government ofCentral Java Province and government of Queensland State of Australia Province for the years 2000until 2007.Key words : Sister Province, Foreign Relation, Foreign Cooperation.